Transvenous lead extraction: the Tandem approach. (19th May 2022) - Akhtar, Z; Zuberi, Z; Leung, LWM; Kontogiannis, C; Waleed, K; Elbatran, AI; Sohal, M; Gallagher, MM
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Transvenous lead extraction (TLE) has become an important strategy in the management of patients with cardiac implantable electronic devices (CIEDs). A rising population of patients with CIEDs coupled with an expanding indication for TLE, has fuelled demand. There are notable procedural risks however development of techniques and tools have contributed to an improvement in the safety and efficacy of TLE. The mechanical rotational dissecting sheath is safe and efficacious whilst the Needle's Eye Snare (NES) is an additional 'bail-out' strategy contributing to procedural success. Purpose: We sought to evaluate the outcomes of TLE performed from the superior access in conjunction with counter-traction provided by snaring of the targeted lead via the femoral access. Method: The 'Tandem' procedure consisted of the rotational powered sheath performing dissection of the adhesions encapsulating the leads (at the superior access), in 'Tandem' with the Needle's Eye Snare providing countertraction via the femoral vein. In brief: after deployment of the locking stylet in the lead lumen, the NES was used to grasp the lead in the right atrium and hold it tort while a rotational sheath was used to dissect through the veins. Once the sheath reached the right atrium, the lead was released from the snare and the sheath was used to continue dissection toward the lead tip. Data for all consecutive 'Tandem' procedures performed between 1/1/2021 – 1/1/2022 in our high-volume TLE institute were collected and evaluated for safety and efficacy. Results: Forty patients aged 69.2±16.3 (70% male), underwent TLE of 75 leads (45 right ventricle, 25, right atrium, 5 left ventricle) with dwell time of 150.1±80.3 months for a non-infectious indication (65%). Of the 40 cases, 27 were hypertensives, 14 had ischaemic heart disease whilst 5 suffered diabetes with a left ventricle ejection fraction of 46.8±10.2%; 12 (30%) were pacing dependent. Procedures were performed by cardiologists in the cardiac catheterisation suite under general anaesthesia (95%) using a locking stylet (100%) with an Evolution RL (11-french 58.7%); a NES 13 millimetres curve (88%) was used to successfully snare 91% of the targeted leads. Complete procedural success was achieved in 92% of leads with 98.7% clinical success. Minor complications occurred in 2 cases (pneumothorax, pocket haematoma requiring intervention), in the absence of any major complications or peri-procedural mortality; there was no 30-day mortality. Conclusion: The 'Tandem' procedure provides an additional strategy to improve the safety and efficacy of TLE, especially in leads of a long dwell time.